Model Pewayangan Punakawan Suku Sasak di Pulau Lombok untuk Meningkatkan Empati Siswa - I Made Sonny Gunawan (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2016)
Empathy is the ability to think and feel person’s situation or condition as a concept that involvescognitive and emotional as form of responses to help someone through communication. Based on thephenomena that often occurred in the fields, there are many students who unconcerned to their friend’sproblem. Unconcern means the people couldn’t feel people’s situation and condition as a concept that involvescognitive and emotional as form of responses to help someone, it can be categorized as low empathy. If theproblems are allowed continuously, it could be imagined that the students will be a crisis of self-awareness tothe importance of empathy to the other people which is illustrated by bad interpersonal relationship. Thesolutions can be offered to improve the empathy through observed puppet learning model. In this case puppetmodel is used as treatments in giving comprehension about the empathy and giving fun learning becauseconsist of humorous aspect. Besides that, by observing the behavior, attitudes, and emotional reactions ofpuppet model is used, students are expected to make a decision what they have to do of their empathy. In thiscase, it refers to the theory of social cognitive. So, person’s empathy would be created through puppet model.